Generalized Elastic Line Deformed on a Nonnull Surface by an External Field in the 3-Dimensional Semi-Euclidean Space E₁³ - Gürbüz, N.; Görgülü, A. (Український математичний журнал, 2015)
We deduce intrinsic equations for a generalized elastic line deformed on the nonnull surface by an external field in the semi-Euclidean space E₁³ and give some applications.